A Study on Strength and Xrd Analysis of Carbonated Concrete - Jothilingam, M.; Pratheeba Paul, Dr.; ., . (International Journal of Engineering and Technology, 2018)
There are number of factors which control the rate of process of natural carbonation and make it very slow in cement based material. Studies show that the effect of carbonation is mostly limited to corrosion of steel reinforcement in R.C.C. structures (including cover depth design and service life prediction). Research at global level is focused on developing a cost effective and safe technology for the possibility of carbon dioxide sequestration as per IPCC guide lines, and attempts are being made to apply the accelerated carbonation technology for CO2 sequestration in concrete.Â  This paper discusses about the detailed study on the uptake quantity of carbon dioxide in concrete, increase of strength and changes in mineral content by adopting. The concrete grades of M15, M20, M25 and M30 were taken for investigating the strength with respect to time of exposure and pressure by adopting Accelerated Carbonation Technology by using commercially available pure CO2 for carbonation curing. After the testing of concrete for strength, XRD analysis was carried out to study the conversion of calcium hydroxide into calcium carbonate due to carbonation.Â  This green technology would help cement, concrete, precast product and other similar manufacturing industries to obtain carbon credit and they can adopt this green technology to reduce their industrial carbon dioxide emissions into the atmosphere to reduce global warming.Â